2019
DOI: 10.3391/mbi.2019.10.4.06
|View full text |Cite
|
Sign up to set email alerts
|

Metabarcoding on planktonic larval stages: an efficient approach for detecting and investigating life cycle dynamics of benthic aliens

Abstract: Amongst the most prominent driving factors behind this were the invasion of the Great Lakes by the zebra mussel Dreissena polymorpha Pallas, 1771 in the 1980s and reports of an average of one new species invading San Francisco Bay every 14 weeks between 1961 to 1995 (Cohen and Carlton 1998). At this time, scientists were becoming well aware of the growing number of introductions worldwide and their impacts on marine communities (Minchin 1996; Reise et al. 1998; Hewitt et al. 1999; Sliwa et al. 2009). Ascidians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 0 publications
3
31
0
Order By: Relevance
“…Zooplankton sampling has been conducted in ships ballast water (Zaiko et al 2015a,b, Ghabooli et al 2016, Darling et al 2018, Lin et al 2020, boats bilge water (Fletcher et al 2017), and in sea water in ports and marinas or nearby natural habitats , Zaiko et al 2015c, Abad et al 2016, Stefanni et al 2018, Couton et al 2019, Leduc et al 2019, Rey et al 2020, Westfall et al 2020. The monitoring of larvae in plankton samples in ports or in the close vicinities, may provide key information about NIS introduction status or detect their presence at an earlier stage (Couton et al 2019). However, targeting dispersive life stages of NIS in the water column has been mostly impractical in routine monitoring using traditional methods.…”
Section: Sampled Locations Substrates and Biological Targetsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zooplankton sampling has been conducted in ships ballast water (Zaiko et al 2015a,b, Ghabooli et al 2016, Darling et al 2018, Lin et al 2020, boats bilge water (Fletcher et al 2017), and in sea water in ports and marinas or nearby natural habitats , Zaiko et al 2015c, Abad et al 2016, Stefanni et al 2018, Couton et al 2019, Leduc et al 2019, Rey et al 2020, Westfall et al 2020. The monitoring of larvae in plankton samples in ports or in the close vicinities, may provide key information about NIS introduction status or detect their presence at an earlier stage (Couton et al 2019). However, targeting dispersive life stages of NIS in the water column has been mostly impractical in routine monitoring using traditional methods.…”
Section: Sampled Locations Substrates and Biological Targetsmentioning
confidence: 99%
“…In the pioneer study of Pochon et al (2013), and despite the co-occurrence of a large number of other eukaryotes, a single spiked Asterias amurensis larvae was detected in plankton samples through metabarcoding. Several other planktonic larval NIS stages have been exclusively detected through metabarcoding (Zaiko et al 2015c, Couton et al 2019, including short-lived larval stages (e.g. Bugula neritina, Corella eumyota; Couton et al 2019), which otherwise may have remained unnoticed for long time.…”
Section: Sampled Locations Substrates and Biological Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…the amplification, sequencing and analysis of marker gene fragments ("molecular barcodes", (Ratnasingham & Hebert, 2007)) of whole communities, can help with rapid processing and identification of species in complex samples. The technique has been shown to be an effective tool for identification of species in zooplankton communities (Brown et al, 2015;Casas, Pearman & Irigoien, 2017;Deagle et al, 2018;Zhang et al, 2018) and for identification of larval stages (Kimmerling et al, 2018;Couton et al, 2019). While several studies have shown the benefits of metabarcoding zooplankton, suitable barcoding regions and primers for amplification are still under discussion (Brown et al, 2015;Bucklin et al, 2016;Chain et al, 2016;Clarke et al, 2017), and current DNA reference databases are far from complete (Bucklin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Research from all sessions is represented by 14 papers that include 12 papers published in a parallel special issue of Aquatic Invasions (see editorial by Fowler et al 2020) and two management focused papers published in this IISSC-VI / ICMB-X joint special issue. Here, Couton et al (2019) shows how metabarcoding represents an efficient approach to the detection and study of reproduction cycle and establishment success of non-indigenous species at an early planktonic larval stage, when species-diagnostic morphological characters are still undeveloped. Further, the study highlights the importance of building local reference collections of DNA barcodes.…”
mentioning
confidence: 99%